2017
DOI: 10.1055/s-0043-102178
|View full text |Cite
|
Sign up to set email alerts
|

Laser lithotripsy resolution for Bouveret syndrome

Abstract: A 75-year-old woman was admitted with epigastric pain, nausea, and vomiting, but without any other symptoms. Laboratory testing and physical examination were normal. Her abdominal computed tomography (CT) scan on admission identified a cholecystoenteric fistula (duodenum to distal antrum) with a 4-cm stone in the duodenum, all of which was compatible with Bouveret syndrome (▶ Fig. 1) We performed a gastroscopy, which identified pyloric obstruction due to a huge stone that was preventing advancement of the endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…One of the most promising techniques for fragmenting stones is laser lithotripsy. 10 Multiple techniques of laser lithotripsy have been utilized, including neodymium: YAG, 11 rhodamine, 12 and holmium: YAG. 10 The benefit of using laser lithotripsy is precise targeting of energy onto the stone with minimal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising techniques for fragmenting stones is laser lithotripsy. 10 Multiple techniques of laser lithotripsy have been utilized, including neodymium: YAG, 11 rhodamine, 12 and holmium: YAG. 10 The benefit of using laser lithotripsy is precise targeting of energy onto the stone with minimal tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Multiple techniques of laser lithotripsy have been utilized, including neodymium: YAG, 11 rhodamine, 12 and holmium: YAG. 10 The benefit of using laser lithotripsy is precise targeting of energy onto the stone with minimal tissue injury. Some lithotripters have an additional capability of differentiating stone from tissue and interrupting signals that may potentially cause tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…The advantage of laser using is splitting the stone with minimal tissue damage. [22,23] Holmium: YAG laser fragmentation has benefits over neodymium and rhodamine laser given the capability of applying high energy via flexible and small probes. [24] Holl et al first reported the success of extracorporeal shockwave lithotripsy in gallstone impacted in duodenum.…”
Section: Discussionmentioning
confidence: 99%